A prospective multicenter study of intermittent chemotherapy with docetaxel and prednisolone for castration-resistant prostate cancer. (28th June 2016) - Narita, Shintaro; Koie, Takuya; Yamada, Shigeyuki; Orikasa, Kazuhiko; Matsuo, Shigeki; Aoki, Hiroshi; Ishidoya, Shigeto; Hoshi, Senji; Tsuchiya, Norihiko; Ohyama, Chikara; Arai, Yoichi; Habuchi, Tomonori
Abstract : Objective: The optimal schedule of docetaxel chemotherapy for castration-resistant prostate cancer is unknown, although continuous administration is accepted as the standard. We conducted a Phase II trial to evaluate the outcome of intermittent docetaxel and prednisolone therapy in castration-resistant prostate cancer. Methods: The patients were treated using a 28-day cycle of docetaxel (70 mg/m 2 on Day 1) and oral prednisolone (10 mg/day). After three consecutive administrations of docetaxel, a holiday was taken until prostate specific antigen levels returned to the baseline. The therapy was continued intermittently until the disease progressed, drug toxicity occurred, or the patients refused further treatment. The primary endpoint was overall survival. Time to treatment failure, adverse events, the duration of chemotherapy holiday and quality of life were also evaluated. Results: A total of 120 patients were enrolled. The median age and pretreatment prostate specific antigen level were 72 years and 37.5 ng/ml, respectively. Sixty (50.0%) patients resumed chemotherapy after the first holiday, and a maximum of six courses were administered to four patients. The median period of the first, second and third-to-fifth holiday was 18.6, 11.0 and 4.9 weeks, respectively. Toxicity was moderate, except for two fatal adverse events. The median time to treatment failure and overall survival from the initiation of docetaxel and prednisolone therapy in all patients were 17.5 and 35.0 months, respectively. All quality-of-life scores were unchanged statistically from the start of docetaxel and prednisolone therapy to the beginning of the second course. Conclusions: Intermittent docetaxel and prednisolone therapy might be a feasible treatment option for castration-resistant prostate cancer with comparable outcome and successful chemotherapy holidays.